Android Mobile Malware Surveillance Exploitation via Call Logs: Proof of Concept - Madihah Mohd Saudi; Farida Hazwani Mohd Ridzuan; Nurlida Basir; Sakinah Ali Pitchay; Nabila N.F.; Ahmad I.N. (Institute of Electrical and Electronics Engineers Inc., 2024)
Indexed by SCOPUS/WOS